The EFSA assessment of Trichilogaster acaciaelongifoliae as biocontrol agent of the invasive alien plant Acacia longifolia: a new area of activity for the EFSA Plant Health Panel?2. (19th July 2016) - Jeger, M. J.; Pautasso, M.; Stancanelli, G.; Vos, S.
Abstract : This paper summarizes the first assessment by the European Food Safety Authority (EFSA) Plant Health (PLH) Panel of a biological control agent (BCA) of an invasive plant. This followed a request by the European Union (EU) Commission to assess the risk to plant health in the EU of an intentional release of the bud‐galling wasp Trichilogaster acaciaelongifoliae for the control of Acacia longifolia . The EFSA PLH Panel also published a statement on the process of assessing the risk of the intentional releases of BCAs of invasive alien plants. Trichilogaster acaciaelongifoliae feeds on A. longifolia and Acacia floribunda . Acacia longifolia is an invasive alien plant species that has a negative effect on biodiversity and ecosystems in Portugal, whereas A. floribunda is not invasive in the EU. Both species are cultivated as ornamental plants in some EU countries. Climatic conditions in the EU are suitable for establishment of T. acaciaelongifoliae where host species are present. This BCA is moderately likely to spread in the EU by natural means, but could be intentionally moved to control A. longifolia in other locations. Its potential effects on invasive A. longifolia and on the cultivated ornamentals were assessed. The EFSA PLH Panel has shown with this work how such advice could be provided in the European Union.